(untitled) (Medical Forum Monthly, 2020)
Objective: To examine the impact of uterine leiomyoma on pregnancy outcome was the objective of this study. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Sandemen Provincial Teaching Hospital Quetta from July 2019 to December 2019. Materials and Methods: Forty four pregnant females with greater than 3cm leiomyoma were included. Those who have less than 3cm leiomyoma were excluded from the study. During antenatal period selected females were properly followed. Size of leiomyoma, parity, maternal age, labour and delivery, pregnancy complications, caesarean section indications and type of delivery were noted. Results: Sixteen (36.4%) females were asymptomatic during pregnancy. Eight (18.2%) females had abd ominal pain, the most common complication during antenatal period. Sixteen (36.4%) delivered through vaginal route and remaining females 28 (63.5%) were delivered through lower segment caesarean section (LSCS) in which elective lower segment caesarean section 18 (41%) and emergency lower segment caesarean section were 10 (23%). 10 (23%) experienced postpartum haemorrhage (PPH) but managed predictably. Due to fibroid in lower segment only two (4.5%) patients ended up in hysterectomy. No perinatal mortality was observed during study. Conclusion: There are high risk pregnancies due to uterine leiomyoma and these pregnancies also increase the caesarean delivery rate as well as increase chances of postpartum haemorrhage and long stay at hospital.